Using Review Sentences in Teaching Grammar - Hendra Sudarso; Haris Dibdyaningsih (STKIP Al Hikmah Surabaya, 2020)
Review sentences is type of grammar practicing which is the easiest way to checking how is the students’ understanding about the previous grammar rules given, especially for college students. We are going to define some steps that we need to apply in review sentences. Moreover, it is still important to upgrading collage students’ grammar understanding because English as EFL will getting hard when they are not really concern about the grammar. This paper will discuss the benefit of review sentences in checking students understanding in the certain type of grammar rules.